2017
DOI: 10.6061/clinics/2017(10)02
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of lung function in pregnant women: Influence of parity and smoking

Abstract: OBJECTIVES:To evaluate pulmonary function in the first and third trimesters of pregnancy and analyze the influence of parity and smoking on spirometry parameters.METHODS:This longitudinal prospective study included a cohort of 120 pregnant women. The inclusion criteria were as follows: singleton pregnancy, gestational age less than 13.86 weeks, and no preexisting maternal diseases. The exclusion criteria were as follows: change of address, abortion, and inadequate spirometry testing. ClinicalTrials.gov: NCT028… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
4
9
1
Order By: Relevance
“…Fourthly, a North-African study showed that high parity leads to a decrease in total airway conductance [6]. On the other hand, the present study findings related to FEV 1 FVC and peripheral airway flows (Table 2) are partially opposite with these of others concluding that multiparity negatively impacts LFD [6, 7, 12, 13, 15] (S2 File). First, a study including females aged ≥ 60 years [7], concluded that compared to females with a parity ≤ 4, those with a parity > 4 had lower FEV 1 , FEV 1 /FVC, MMEF and PEF.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Fourthly, a North-African study showed that high parity leads to a decrease in total airway conductance [6]. On the other hand, the present study findings related to FEV 1 FVC and peripheral airway flows (Table 2) are partially opposite with these of others concluding that multiparity negatively impacts LFD [6, 7, 12, 13, 15] (S2 File). First, a study including females aged ≥ 60 years [7], concluded that compared to females with a parity ≤ 4, those with a parity > 4 had lower FEV 1 , FEV 1 /FVC, MMEF and PEF.…”
Section: Discussioncontrasting
confidence: 55%
“…Secondly, another study including females aged ≥ 40 years [6], concluded that multiparity leads to a tendency towards an OVD with a decrease in FEV 1 /FVC. Thirdly, compared to Brazilian nulliparous females aged < 25 years, those with a parity ≥ 1 had lower MMEF during the first trimester and lower PEF during the third trimester [15]. Fourthly, it appears that parity accelerated lung-aging, with an increase of one parity rising the estimated lung-age by 1.2 years [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 An upward movement of the diaphragm in the later stages of pregnancy is an indication of the pressure developed by the uterus on the abdomen, mitigating negative intrapleural pressure and hyperventilation with a decrease in the partial pressure of carbon dioxide. 5,6 Transverse diameter of the chest increases due to the expanded subcostal angle that resists the effect of expanding the uterus and the upward movement of diaphragm to provide change in the pulmonary function as required for the pregnancy. 7 In the Western part of the globe, parity and smoking are associated with the lung function of pregnant women, which is evaluated by a spirometer.…”
Section: Introductionmentioning
confidence: 99%